Contemporary feminist theologies : power, authority, love - Handasyde, Kerrie; Pryor, Rebekah; McKinney, Cathryn (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book explores the issues of power, authority and love with current concerns in the Christian theological exploration of feminism and feminist theology. It addresses its key themes in three parts. Power deals with feminist critiques; Authority unpacks feminist methodologies; and Love explores feminist ethics. Covering issues such as embodiment, intersectionality, liberation theologies, historiography, queer approaches to hermeneutics, philosophy and more, it provides a multi-layered and nuanced appreciation of this important area of theological thought and practice. This volume will be vital reading for scholars of Feminist Theology, Queer Theology, Process Theology and Practical Theology, as well as Religion and Gender"--
OCLC-licensed vendor bibliographic record.
Keywords: Feminist theology; Feminism -- Religious aspects -- Christianity; RELIGION / Christianity / Theology / General; RELIGION / Sexuality & Gender Studies; SOCIAL SCIENCE / Feminism & Feminist Theory